Numerical simulation of wavy film condensation in a vertical channel with non-condensable gas. (March 2020) - Choi, Yunmin; Son, Gihun; Lee, Gilbong
Highlights: A numerical approach is presented for wavy film condensation in a vertical channel with non condensable gas. A theoretical formulation is derived for steady film condensation with non condensable gas. The condensation rate of pure vapor increases significantly in a wavy interface regime of Ref  >  30   40. The presence of non condensable gas has a greater influence on the heat transfer in wavy film condensation than in steady film condensation. Abstract: A numerical approach for wavy film condensation in internal vapor flows containing non-condensable gas is developed by combining unsteady differential equations for the vapor region with unsteady integral boundary-layer formulations for a thin liquid region. The present approach, which can save computational time significantly, can accurately consider the condensation effect by explicitly implementing the velocity, mass flux, stress and heat flux conditions at the liquid-vapor interface. A theoretical formulation is also presented for steady film condensation containing non-condensable gas. The numerical results for steady film condensation match well with the theoretical solutions. Computations are performed to analyze the combined effects of wavy interface motion and non-condensable gas on film condensation.